Respuesta :

Answer:

The graph is attached below.

Step-by-step explanation:

Considering the exponential function

[tex]y=3^{-2x}[/tex]

[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^{bx}=\left(a^b\right)^x[/tex]

[tex]3^{-2x}=\left(3^2\right)^{-x}[/tex]

       [tex]=\left(3^2\right)^{-x}[/tex]

       [tex]=9^{-x}[/tex]

The graph is also attached below.

Keywords: exponential function, graph

Learn more about exponential function from brainly.com/question/11908487

#learnwithBrainly

Ver imagen SaniShahbaz